2003
DOI: 10.1046/j.1475-1313.2003.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of information included on the GOS 18 referral form used by optometrists

Abstract: Purpose: To audit the information included on GOS 18 forms used by UK optometrists when referring patients to an ophthalmologist. Methods: All GOS 18 forms received in a hospital ophthalmology department over a 10-week period were photocopied and the categories of information presented were recorded. Results: A total of 444 forms were analysed. The two most common referral categories were cataract 36.7% (n ¼ 163) and glaucoma 18.4% (n ¼ 82). Only 7% (n ¼ 11) of cataract referrals included details regarding eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
6
27
0
Order By: Relevance
“…1996). The reported referral patterns corresponded well with those of UK optometrists (Lash 2003). We did not investigate the relevance of the referrals.…”
Section: Discussionsupporting
confidence: 74%
“…1996). The reported referral patterns corresponded well with those of UK optometrists (Lash 2003). We did not investigate the relevance of the referrals.…”
Section: Discussionsupporting
confidence: 74%
“…2,4,5 Up to 12% of optometrist referrals were made for isolated VF loss in the absence of any glaucoma damage. 7,8 A separate study reported an increase in false-positive referrals from 1988 to 1993, and this was felt to be due to the increase in VF testing and to an increased willingness to refer patients at lower IOPs. 6 As referrals have been shown to be more accurate when IOP measurement, VF testing, and optic disc assessment were all performed, 2,3 it was important that any glaucoma detection programme involving optometrists should involve all three parameters.…”
Section: Discussionmentioning
confidence: 99%
“…From previous papers, the reported proportion of referrals containing information for these three parameters ranged from 15 to 82%. 2,3,8 To further increase the positive predictive value of referrals, it has also been recommended that IOP measurements and visual fields should be repeated. 3 Under the old GOS contract, when patients attended their community optometrist, refraction was mandatory, and there was no provision for supplemental examinations such as applanation tonometry and perimetry, to be performed regardless of clinical need.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] There is a wide variation of optometric practice across the profession for glaucoma detection, with tests such as tonometry and visual fields, being left to the discretion of the optometrist. [6][7][8] Several approaches have been reported in the literature aimed at improving glaucoma case-finding.…”
Section: Introductionmentioning
confidence: 99%